Pengembangan Bahan Ajar Matematika Realistik Menggunakan Aplikasi New Powtoon - Pramudiani, Puri; Aslam; Sari, Prima Mutia (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2023)
21st century learning makes technology cannot be separated with the development of teaching materials, including learning mathematics. The use of technology in learning can be associated with efforts to improve students' critical thinking skills. Based on the results of the preliminary study conducted by Community Partnership Program (PKM) Team, Universitas Muhammadiyah Prof. Dr. Hamka in SDN 066 Halimun has never had training or assistance in developing teaching materials using new powtoon application. Therefore, this activity aims to develop the competence of SDN 066 Halimun teachers in an effort to improve students' critical thinking skills using a realistic mathematics approach based on new powtoon application. According to the learning assistance activities carried out by PKM Team, teachers can further develop their teaching skills because the media used is quite helpful in illustrating the mathematical ideas or concepts. Likewise, the students were very happy and have better understanding toward the concept of mathematical learning given. From this activity, it is recommended that new powtoon application can become an alternative media in realistic mathematics learning.